Intensity-modulated Radiotherapy for Anal Cancer: Dose–Volume Relationship of Acute Gastrointestinal Toxicity and Disease Outcomes. Issue 10 (October 2018) - Ng, M.; Ho, H.; Skelton, J.; Guerrieri, M.; Guiney, M.; Chao, M.; Blakey, D.; Macleod, C.; Amor, H.; Subramanian, B.; Melven, L.
Abstract: Aims: Intensity-modulated radiotherapy (IMRT) is increasingly used in the treatment delivery of chemoradiotherapy in anal cancer with the ability to reduce toxicity. We report on 4 year outcomes since the introduction of IMRT and identify the most predictive bowel organ at risk that correlates with acute diarrhoea. Materials and methods: Fifty-eight patients receiving definitive chemoradiotherapy for squamous or basaloid cell anal carcinoma (T1-4NanyM0) were reviewed. Fifty-four per cent of patients had stage III disease and most (79%) were treated with a dose of 54 Gy in 30 fractions. Patient acute gastrointestinal toxicity was recorded using Common Terminology Criteria of Adverse Events (CTCAE) diarrhoea grading. Four different methods of bowel were re-contoured for each patient and correlated with acute diarrhoea. Locoregional control and overall survival were analysed. Results: CTCAE grade 3 or more diarrhoea occurred in 11/58 patients (19%). Seven patients did not complete treatment; 10 patients (17%) required a treatment break of 3 or more days. 'Bowel cavity' was the best predictor of acute grade 3 toxicity using volume ( P = 0.002) or volume to bowel cavity in 5 Gy bins (V5–V50Gy); P < 0.05. Bowel cavity V30Gy ≤ 300 cm 3 predicts a 6% grade 3 diarrhoea risk versus > 300 cm 3 predicts a 42% risk. Four year progression-free survival was 84% (95% confidence interval 73–92%) and overall survival was 88% (95% confidence interval 75–95%). Conclusion: Chemoradiation using IMRT provides excellent local control and acceptable acute gastrointestinal toxicity. Bowel cavity is the most sensitive predictor for grade 3 versus grade 0–2 diarrhoea, with any volume receiving 5–50 Gy discriminatory. Highlights: IMRT for anal cancer provides excellent local control and overall survival. Severe acute gastrointestinal toxicity is low, treatment breaks short and most patients completed treatment. Bowel cavity dose is the best predictor of acute severe diarrhoea compared with other contouring methods. Bowel cavity V30Gy ≤ 300 cm 3 predicts a 6% grade 3 diarrhoea risk versus >300 cm 3 predicts a 42% risk.